Blood flow restricted exercise and discomfort: a review - Spitz, R. W.; Wong, V.; Bell, Z. W.; Viana, R. B.; Chatakondi, R. N.; Abe, T.; Loenneke, J. P. (The Journal of Strength and Conditioning Research, 2022)
Blood flow restriction exercise involves using a pneumatic cuff or elastic band to restrict arterial inflow into the muscle and block venous return out of the muscle during the exercise bout. The resultant ischemia in conjunction with low-load exercise has shown to be beneficial with increasing muscle size and strength. However, a limitation of using blood flow restriction (BFR) is the accompanying discomfort associated with this type of exercise. Factors that may influence discomfort are applied pressure, width of the cuff, cuff material, sex, and training to failure. The goal of this review was to evaluate the existing literature and elucidate how these factors can be manipulated to reduce discomfort during exercise as well as provide possible directions for future research. Thirty-eight different studies were located investigating BFR and discomfort. It was found that BFR training causes more discomfort than exercise without BFR. However, chronic use of BFR may increase tolerability, but discomfort may still be elevated over traditional non-blood flow restricted exercise. Discomfort can be attenuated by the application of lower applied pressures and stopping short of task failure. Finally, in the upper body, wider cuffs seem to increase ratings of discomfort compared with more narrow cuffs. In conclusion, applying the proper-sized cuff and making the applied pressure relative to both the individual and the cuff applied may attenuate discomfort. Reducing discomfort during exercise may help increase adherence to exercise and rehabilitation programs.